TO STUDY THE VOCATIONAL EDUCATION OF SECONDARY LEVEL GIRL STUDENTS STUDYING IN ENGLISH & HINDI MEDIUM OF DISTRICT GHAZIABAD AND BAGHPAT - Poonam; Sharma, Kavita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Vocational education helps to prepare students for a specific career. This type of education can take place in trade schools, technical schools or on-the-job training programs. These trades or crafts include, but are not limited to, plumbing, nursing and architecture. Vocational education usually consists of a mix of theory and practical, hands-on experience. Typically, instructors use competency-based grading, over a standard grading scale, to check if students have mastered a skill. Modern vocational education allows students to develop transferable creative and personal development skills specific to a chosen job. The objective of this study is to know the difference in context to vocational education between female students studying in English and Hindi medium in district Ghaziabad and Baghpat.